2021
DOI: 10.1108/jmp-03-2021-0181
|View full text |Cite
|
Sign up to set email alerts
|

Passion in the pit: the effects of harmonious and obsessive passion on nurse burnout

Abstract: PurposeAnecdotal and survey reports indicate that nurses are suffering increased stress and burnout due to the coronavirus disease (COVID-19) pandemic. Therefore, this study investigated two forms of passion, harmonious and obsessive passion, as resources that may indirectly predict two forms of burnout, disengagement and exhaustion, through the mediator of job stress.Design/methodology/approachThe authors tested their hypotheses in a mediation model using a sample of nurses surveyed at three timepoints during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 48 publications
(83 reference statements)
1
10
0
1
Order By: Relevance
“…Prior studies have investigated the causes of emotional exhaustion, such as excessive job demands, a lack of social support, interpersonal conflict, etc. However, Landay et al [ 3 ] argued that a strong inclination toward work that people love, which makes them invest more time and energy in one activity, becomes the potential cause of emotional exhaustion. This strong inclination toward work is called a passion for work.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Prior studies have investigated the causes of emotional exhaustion, such as excessive job demands, a lack of social support, interpersonal conflict, etc. However, Landay et al [ 3 ] argued that a strong inclination toward work that people love, which makes them invest more time and energy in one activity, becomes the potential cause of emotional exhaustion. This strong inclination toward work is called a passion for work.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, passion for work has gained considerable academic and managerial attention [ 3 , 5 , 6 ]. A decade ago, the dualistic model of passion (DMP) proposed that there are two types of passion: harmonious and obsessive passion [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many of the articles in the special issue specifically deal with the variety of stresses faced by those in the nursing profession. For example, Landay et al (2022) investigate the subject of burnout in nurses by focusing specifically on how harmonious and obsessive passion for their work might mitigate or exacerbate feelings of burnout. Interestingly, they found that both forms of passion showed evidence of providing protective factors against stress and burnout.…”
mentioning
confidence: 99%